2001
DOI: 10.1051/vetres:2001112
|View full text |Cite
|
Sign up to set email alerts
|

Residual foot-and-mouth disease virus antibodies in French cattle and sheep six years after the vaccination ban

Abstract: -A serological survey was carried out on French cattle to establish a reference pattern of residual vaccine antibodies and non-specific reactions against the foot-and-mouth disease virus 6 years after the ban on vaccination and in the absence of any foot-and-mouth disease outbreak. Most of the multi-vaccinated cattle still displayed high titres of antibodies and up to 50% of those which had received a single injection still had antibodies. Non-specific reactors were also recorded among animals born during and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
2
1
Order By: Relevance
“…Some studies stated that infection-induced FMD NSP antibodies could persist for a long duration [40,41]. Another study reported that neutralising antibodies could persist for several years [42]. In our study, even though seroprevalence of the cattle aged more than three years group was higher than less than or equal to 3 years group, statistical analysis showed no signi cant difference between seroprevalence of these groups.…”
Section: Discussioncontrasting
confidence: 60%
“…Some studies stated that infection-induced FMD NSP antibodies could persist for a long duration [40,41]. Another study reported that neutralising antibodies could persist for several years [42]. In our study, even though seroprevalence of the cattle aged more than three years group was higher than less than or equal to 3 years group, statistical analysis showed no signi cant difference between seroprevalence of these groups.…”
Section: Discussioncontrasting
confidence: 60%
“…Different vaccines, even with the same potency, have been seen to provide different levels of immunity and protection 41 . Vaccines used for FMD eradication in Europe stimulated high and long-lasting antibody levels for years after cattle had been vaccinated several times 3 42 43 , however, this may not be the case for other vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Following infection, animals can remain seropositive to structural antibodies of FMDV for several years (Doel, 2005) and antibodies to the 3ABC NS protein have been found to be still detectable at 1–2 years after infection of experimental animals (Clavijo et al., 2004). Although FMD vaccination does not produce a long lasting protection, antibodies due to vaccination can be found several years after the cessation of vaccination, especially in multiply vaccinated animals (Remond et al., 2001; Terpstra et al, 1990). However, if vaccination had been the cause of the antibodies found it would not have been expected to have found so many animals with antibodies against both non‐structural and structural proteins of FMDV, since vaccination preferentially elicits antibodies to structural proteins.…”
Section: Discussionmentioning
confidence: 99%